Pengaruh Economic Value Added (EVA) Dan Market Value Added (MVA) Terhadap Harga Saham Perusahaan Manufaktur Sub Sektor Logam Di Bursa Efek Indonesia Periode 2013-2017 - Siti Zulfa Tsuroyya Effendi (Universitas Batanghari Jambi, 2020)
This research is a quantitative research that aims to analyze the effect of Economic Value Added (EVA) and Market Value Added (MVA) on stock prices both partially and simultaneously. The sampling in this study used a purposive sampling method, so that a sample of 13 companies was obtained. The data obtained was analyzed using multiple linear regression analysis techniques. The results of the statistical t test prove that partially Economic Value Added (EVA) and Market Value Added (MVA) have a significant effect on stock prices. This is evidenced by the significance value (sig) obtained which is 0.028, where this value is smaller than 0.05. While the results of the statistical F test prove that simultaneously Economic Value Added (EVA) and Market Value Added (MVA) have a significant effect on stock prices. This is evidenced by the significance value (sig) obtained which is 0.031, where this value is smaller than 0.05. The contribution of the influence of EVA and MVA on stock prices is 21.9%. Based on the results of the research obtained, it is advisable for investors to continue to pay attention to the company's financial performance before making a stock selection, which is measured through the approach of Economic Value Added (EVA) and Market Value Added (MVA).